Explore IDNLearn.com to discover insightful answers from experts and enthusiasts alike. Our platform provides accurate, detailed responses to help you navigate any topic with ease.
Step-by-step explanation:
You want to demonstrate the identity ...
(1-tan⁴(A))·cos⁴(A) = 1 -2·sin²(A)
Working with the left side, we have ...
[tex](1-\tan^4(A))\cos^4(A)=1-2\sin^2(A)\\\\(1-\dfrac{\sin^4(A)}{\cos^4(A)})\cos^4(A)=1-2\sin^2(A)\qquad\text{use tangent identity}\\\\\cos^4(A)-\sin^4(A)=1-2\sin^2(A)\qquad\text{multiply it out}\\\\(\cos^2(A) +\sin^2(A))(\cos^2(A)-\sin^2(A))=1-2\sin^2(A)\qquad\text{factor}\\\\1((1-\sin^2(A))-\sin^2(A)) = 1-2\sin^2(A)\qquad\text{use $\cos^2$ identity}\\\\1-2\sin^2(A)=1-2\sin^2(A)\qquad\text{Q.E.D.}[/tex]
__
Additional comment
The referenced identities are ...
tan = sin/cos
cos² = 1 -sin²
and the factorization of the difference of squares:
a² -b² = (a +b)(a -b).